In situ analysis of hepatitis B virus (HBV) antigen and DNA in HBV-induced hepatocellular carcinoma - Ye Zheng; Mingzhu Xu; Dong Zeng; Haitao Tong; Yuhan Shi; Yanling Feng; Xiaonan Zhang (BMC, 2022)
Abstract Aims Hepatitis B Virus (HBV) infection is the major risk factor for hepatocellular carcinoma (HCC) in East Asia. Here we aimed to further investigate the abundance of viral antigen and DNA within HBV-related HCC and surrounding tissues at histological level. Method In addition to routine histopathology, in situ hybridization (ISH) of HBV DNA and immunohistochemistry (IHC) of HBsAg were performed in tissues from 131 HBsAg-positive HCC patients undergoing liver resection. Serum α-fetoprotein together with basic biochemical and immunological parameter was also measured. Results Overall, the ISH of HBV DNA and IHC of HBsAg showed 31.3% and 92.9% positive rate respectively (p < 0.0001). The level of correlation between these two markers was much more significant in tumor (p < 0.0001) than in tumor-surrounding tissue (p = 0.01). HBsAg exhibited a much higher positive rate in tumor-adjacent tissue than in tumor tissue (86.6% versus 29.9%, p < 0.0001) with significantly different staining pattern. By contrast, the positive rate of HBV DNA ISH was comparable in tumor and surrounding tissue (17.6% versus 22.9%, p = 0.36). Yet the HBV DNA signal in tumor tissue showed predominant nuclear localization (87.0%) whereas staining pattern in adjacent tissue was mixed (43.3% nuclear localization, p = 0.0015). Finally, no significant association between intra-tumor HBV DNA/HBsAg positivity and major histological markers (microvascular invasion, tumor differentiation, etc.) or recurrence after surgery was observed. Conclusions These data confirmed the largely integrated state of HBV DNA, weaker expression and altered localization of surface antigen in tumor compared with surrounding tissue. The strikingly different prevalence and localization of HBsAg and HBV DNA reflected the complex and heterogeneous mechanisms leading to HBV-induced tumorigenesis.